BIT: A Tool for Instrumenting Java Bytecodes - Zorn, Ben; Lee, Han Bok (Advanced Computing Systems Association, 1997)
BIT (Bytecode Instrumenting Tool) is a collection of Java classes that allow one to build customized tools to instrument Java Virtual Machine (JVM) bytecodes. Because understanding program behavior is an essential part of developing effective optimization algorithms, researchers and software developers have built numerous tools that carry out program analysis. Although there are existing tools that analyze and modify executables on a variety of operating systems and machine architectures, there currently is no framework for carrying out the same task for JVM bytecodes. In this paper, we describe BIT, which allows the user to insert calls to analysis methods anywhere in the bytecode, so that information can be extracted from the user program while it is being executed. In this paper, we describe several simple tools built using BIT and also report on BIT's performance. WE found that the overhead for the execution speed and size were between 23% to 150%.